To Lead Chaste Lives: Father John Francis Harvey and the Pastoral Care of Catholic Homosexuals - Babits, Chris (US catholic historian, 2024)
This article examines the religious and therapeutic world of American priest Father John Francis Harvey (1918–2010), founding director of Courage, an apostolate of the Catholic Church centered on ministering to Catholic homosexuals. The following offers a close reading of Harvey's first full-length book, The Homosexual Person: New Thinking in Pastoral Care, published in 1987. I argue that though Harvey borrowed from the psychological thought that influenced the Protestant ex-gay movement, he offered a distinctly Catholic form of pastoral counseling for homosexuals that advanced Courage's religious and therapeutic goal of chastity, rather than the Protestant ex-gay ministry groups' focus on heterosexual conversion.